SELECTED ISSUES IN THE DIPLOMATIC RELATIONS BETWEEN THE REPUBLIC OF KOREA AND THE REPUBLIC OF VIETNAM (1955–1957): A VIEW FROM CHOI DUK SHIN'S VIETNAM-RELATED DIPLOMATIC DOCUMENTS - Ha Chi, Nguyen (Tạp chí Khoa học Trường Đại học Sư phạm Hà Nội: Khoa học Xã hội, 2025)
This article investigates new aspects of the diplomatic relations between the Republic of Korea and the Republic of Vietnam from 1955 to 1957, through the analysis of Choi Duk Shin’s diplomatic reports. Through a comprehensive analysis of primary sources, including archival documents from both Korea and the U.S., the study reexamines these relations beyond the established focus on military cooperation. It investigates how anti-communism, Japan's economic and political influence, and the overseas Chinese community shaped bilateral dynamics. Content analysis of Choi Duk Shin’s diplomatic reports provides valuable insights into South Korea's diplomatic strategies during the Cold War. Additionally, an interdisciplinary approach examines non-military factors, including Japan’s influence and the overseas Chinese community, providing a deeper look into often-overlooked underlying influences. By highlighting these factors, the paper contributes new insights into how the Republic of Korea's foreign policy toward Vietnam evolved within a broader regional landscape, challenging previous studies with a nuanced understanding of non-military elements influencing the relationship.